2021
DOI: 10.1016/j.amepre.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in Hepatitis C Testing and Treatment During the COVID-19 Pandemic

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic has disrupted healthcare services, reducing opportunities to conduct routine hepatitis C virus (HCV) antibody screening, clinical care, and treatment. Therefore, people living with undiagnosed HCV during the pandemic may later become identified at more advanced stages of the disease, leading to higher rates of morbidity and mortality rates. Further, unidentified HCV-infected individuals may continue to unknowingly transmit the virus to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…In contrast, the number of hepatitis C tests decreased but the number of de novo hepatitis C diagnoses among those tested also decreased. These results are in contrast with those from models predicting increased nondiagnosed cases of hepatitis C in Spain during the COVID-19 epidemics [24] but they are in accordance with recent real data from the USA [25]. De novo hepatitis C diagnosis in our setting has been more commonly linked to high-risk sexual practices and sexualized substance use [26].…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, the number of hepatitis C tests decreased but the number of de novo hepatitis C diagnoses among those tested also decreased. These results are in contrast with those from models predicting increased nondiagnosed cases of hepatitis C in Spain during the COVID-19 epidemics [24] but they are in accordance with recent real data from the USA [25]. De novo hepatitis C diagnosis in our setting has been more commonly linked to high-risk sexual practices and sexualized substance use [26].…”
Section: Discussionsupporting
confidence: 78%
“…The substantial gap in hepatitis and HIV infections knowledge points to the urgent need for developing and implementing population educational programs. This is even more urgent in the era of COVID-19 epidemic, as it has been shown that COVID-19 epidemic may have disrupted hepatitis and HIV prevention and treatment services (40)(41)(42) whereas it may have widened health and economic inequalities (43).…”
Section: Discussionmentioning
confidence: 99%
“…The substantial gap in hepatitis and HIV infections knowledge points to the urgent need for developing and implementing population educational programs. This is even more urgent in the era of COVID-19 epidemic, as it has been shown that COVID-19 epidemic may have disrupted hepatitis and HIV prevention and treatment services (40)(41)(42) whereas it may have widened health and economic inequalities (43).…”
Section: Discussionmentioning
confidence: 99%